2006
DOI: 10.2166/wst.2006.356
|View full text |Cite
|
Sign up to set email alerts
|

Fate of nonylphenol polyethoxylates and nonylphenoxy acetic acids in an anaerobic digestion process for sewage sludge treatment

Abstract: Many environmental problems caused by endocrine disruptors (EDs) have been reported. It is reported that EDs flow into sewage treatment plants, and it has been pointed out that these may be shifted from the wastewater treatment process to the sludge treatment process. Little is known about the fate of EDs accumulated in sewage sludge, so we carried out a study to clarify the fate of EDs in sewage sludge treatment processes, especially in an anaerobic digestion process. In this study, nonylphenol (NP) was selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 0 publications
2
10
0
2
Order By: Relevance
“…The nonylphenoxy acetic acids are finally decomposed to nonylphenol carboxylate [24], which could explain the smaller increase in the concentration of NP observed after the aerobic digestion (figure 4b) compared with that obtained after the anaerobic digestion (figure 4a), consistent with the study of Knudsen et al [23]. [19].…”
Section: Dehp Dehp Was Found In All Sludge Samples Analysed (Table 2)supporting
confidence: 89%
See 1 more Smart Citation
“…The nonylphenoxy acetic acids are finally decomposed to nonylphenol carboxylate [24], which could explain the smaller increase in the concentration of NP observed after the aerobic digestion (figure 4b) compared with that obtained after the anaerobic digestion (figure 4a), consistent with the study of Knudsen et al [23]. [19].…”
Section: Dehp Dehp Was Found In All Sludge Samples Analysed (Table 2)supporting
confidence: 89%
“…The concentration of the sum of NP, NP1EO, and NP2EO was considerably higher than the limit value of 50 mg kg À1 dm fixed in the third draft of the future European Sludge Directive in all samples analysed ( figure 3). It has been reported that under anaerobic conditions, NP2EO is degraded to NP1EO, and NP1EO is degraded to NP [23,24]. This fact explains the decrease in concentrations for NP1EO and NP2EO from primary and secondary sludge to anaerobically digested sludge (figure 4a) and the high concentration of NP in anaerobically digested sludge compared with the concentrations in primary and secondary sludge samples.…”
Section: Dehp Dehp Was Found In All Sludge Samples Analysed (Table 2)mentioning
confidence: 84%
“…It was also postulated that increased NP concentrations may arise from NP 1 EO, which is anaerobically degraded even though these hydrophobic metabolites were released in small amounts. The study failed to identify the quantities of NPECs that can also anaerobically degrade to form NP (Minamiyama et al, 2006). The notion of NPECs contributing to the NP levels detected in the environment has been suggested by Conn et al (2006).…”
Section: Precursors Of Aps and Short Chained Apeosmentioning
confidence: 97%
“…It is generally thought that NP 1 ECs is transformed to NP only under anaerobic conditions (Ahel et al, 1994a;Minamiyama et al, 2006) and anoxic conditions (Ike et al, 2002). Recently Liu et al (2006) reported the formation of NP from NP 2 EO with NP 1 EC and NP 2 EC as the intermediate metabolites, which were further transformed to shorter NPEOs under aerobic conditions by Ensifer sp.…”
Section: Further Transformation and Ultimate Degradationmentioning
confidence: 99%
“…It has been reported that under anaerobic conditions NP2EO is degraded to NP1EO and NP1EO is degraded to NP (Knudsen et al, 2000;Minamiyama et al, 2006). This fact, together with the loss of weight achieved during the sludge dehydration process, explains the high concentration levels of NP in anaerobically-digested dehydrated sludge compared to the concentration levels in primary and secondary sludge samples and the decrease of the concentrations of NP1EO and NP2EO from primary and secondary sludges to anaerobically-digested dehydrated sludge (Table 2).…”
Section: Npementioning
confidence: 92%